Odpowiedzi

2010-02-18T14:04:39+01:00
-4-4(4-4(4-16+4x))=44
-4-4(4-16+64-16x)=44
-4-16+64-256+64x=44
-276+64+64x=44
64x=44+212
64x=256/64
x=4

x-2(x-3x+12)30-5x
x-2x+6x-24=30-5x
5x+5x=30+24
10x=54/10
x= 5,4

Najlepsza Odpowiedź!
2010-02-18T14:05:59+01:00
-4-4{4-4[4-4(4-x]}=44
-4-4[4-4[4-16+4x]]=44
-4-4[4-16+64-16x]=44
-4-16+64-256+64x=44
64x=44-64+4+16+256
64x=256
x=4


x-2[x-3(x-4)]=5(6-x)
x-2[x-3x+12]=30-5x
x-2x+6x-24=30-5x
7x-2x+5x=30+24
10x=54
x=5,4


2x-1/3x+2/5=1/3(4+5x)-7/30
2x-1/3x+2/5=4/3+5/3x-7/30
2x-6/3x=4/3-7/30-2/5
2x-2x=40/30-7/30-12/30
0=21/30

równanie fałszywe